PENGARUH MEDIA TAKALINTAR BERBANTUAN QUIZIZZ PADA MATERI PERKALIAN BILANGAN CACAH TERHADAP HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Noor Faizah, Apriliya; Cahya Rohim, Dhina; Awalludin Nugraha, Yoga (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The research is motivated by the low mathematics learning outcomes of third-grade elementary school students on multiplication of whole numbers, caused by a lack of innovative learning media, resulting in monotonous and uninteresting learning. This study aims to determine the effect of Takalintar media supported by Quizizz on student learning outcomes and to assess student responses to its use. This studyemployed a quantitative approach with a quasi-experimental design and a nonequivalent control group design. The study population consisted of 30 students, consisting of 16 in the experimental class and 14 in the control class. The sampling technique used purposive sampling. Data were collected through tests (pretest and posttest), questionnaires, interviews, and documentation. Data analysis included normality tests, homogeneity tests, independent sample t-tests, paired sample ttests, and N-Gain tests using SPSS. The results indicate that Takalintar media supported by Quizizz has an impact on the learning outcomes of third-grade emenetary school students. This is indicated by higher posttest scores in the experimental class than in the control class. Keywords: Takalintar Media, Quizizz, Learning outcomes, Multiplication of whole numbers, Elementary School.